2002
DOI: 10.1111/j.1547-5069.2002.00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Retention in Community‐based Clinical Trials

Abstract: As more funding agencies emphasize clinical trials, more investigators will be held accountable for credible and generalizable findings based on retaining the projected number of study participants. The small number of published reports for the decade that identified both retention strategies and outcomes substantiates the need to better document these factors in future research reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
137
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(148 citation statements)
references
References 49 publications
10
137
1
Order By: Relevance
“…Secondly, Facebook can assist with identifying participants who are at risk of loss to follow up given that those who were re-engaged were younger, unmarried, had a lower household income, less education, and were more likely to identify as non-Caucasian compared to ongoing participants. This is consistent with other studies where more vulnerable groups are more susceptible to lost to follow-up [20,21]. Of note, among those lost to follow-up, there were no differences between those who were found through Facebook and those that were not identified.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Secondly, Facebook can assist with identifying participants who are at risk of loss to follow up given that those who were re-engaged were younger, unmarried, had a lower household income, less education, and were more likely to identify as non-Caucasian compared to ongoing participants. This is consistent with other studies where more vulnerable groups are more susceptible to lost to follow-up [20,21]. Of note, among those lost to follow-up, there were no differences between those who were found through Facebook and those that were not identified.…”
Section: Discussionsupporting
confidence: 81%
“…However when considering the literature surrounding finding, contacting and re-engaging lost to followup participants our sample size is consistent with other studies [16,21]. An additional limitation is that only one social media platform was used to re-contact participants, and these efforts were limited to a three month period.…”
Section: Discussionsupporting
confidence: 52%
“…, in review of 21 community-based trials, identified 9 themes and noted that those studies with the highest retention rate appeared to use a combination of strategies [11]. Hunt and White (1998) chose to review four longitudinal studies to develop a list of general strategies to maximize retention [16].…”
Section: Discussionmentioning
confidence: 99%
“…We included studies that provided data on retention rates, described data from a primary study, and provided information regarding strategies used to retain participants. We searched PubMed (August 11, 2005) 11, 2005). The search strategies combined text words and controlled vocabulary words for concepts of 'attrition', 'retention', 'patient dropouts' and 'loss to follow-up'.…”
Section: Searching and Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation